Cholesterol metabolism and glaucoma: Modulation of Muller cell membrane organization by 24S-hydroxycholesterol. (October 2017) - Gambert, Ségolène; Gabrielle, Pierre-Henry; Masson, Elodie; Leger-Charnay, Elise; Ferrerro, Arthur; Vannier, Arthur; Gendrault, Clément; Lachot, Méline; Creuzot-Garcher, Catherine; Bron, Alain; Gregoire, Stéphane; Leclere, Laurent; et al.
Highlights: Muller Glial Cell activation is induced in retinal gliosis during glaucoma. 24S-hydroxycholesterol (24S-OHC) is overexpressed during glaucoma. Cholesterol, sphingomyelin, saturated faaty acids and ganglioside GM-3 are enriched in raft fractions. Protein implicated in adhesion or oxidative stress pathways in raft fractions were up and down-regulated by the 24S-OHC treatment. Further studies are needed to better characterize the surrounded mechanisms. Abstract: Glaucoma is a progressive and irreversible blinding neuropathy that is characterized by the loss of retinal ganglion cells (RGCs). Muller Glial Cell (MGC) activation is induced in retinal gliosis. MGCs are the most numerous glial cells in the retina and one of their roles is to sustain cholesterol homeostasis. 24S-hydroxycholesterol (24S-OHC) is one of the form of cholesterol elimination from the retina and is overexpressed during glaucoma. The objective of this study was to determine whether 24S-OHC triggers MGC membrane dynamics involving lipid rafts and contributes to gliosis at early and late time points. A proteomic analysis was carried out by nanoLC–MS/MS in raft and non-raft fractions from MGCs after treatment with 24S-OHC (10 μM). The expression of structural and functional proteins was further analyzed by Western-blotting, as well as the levels of GM3 ganglioside by LC–MS. Cholesterol, sphingomyelin, saturated fatty acids and ganglioside GM3 are enriched in the rafts fractions in MGCs. Caveolin-1, flotillin-1, connexin-30 and -43 are localized in the MGCs rafts. Proteins implicated in adhesion or oxidative stress pathways in raft fractions were up and down-regulated by the treatment. Our data showed that 24S-OHC induced early changes in protein distribution in raft microdomains; however, further studies are needed to better characterize the surrounded mechanisms.